The clinical significance of B-cell maturation antigen as a therapeutic target and biomarker. (3rd April 2018) - Sanchez, Eric; Tanenbaum, Edward J.; Patil, Saurabh; Li, Mingjie; Soof, Camilia M.; Vidisheva, Aleksandra; Waterman, Gabriel N.; Hekmati, Tara; Tang, George; Wang, Cathy S.; Chen, Haiming; Berenson, James
ABSTRACT: Introduction : B-cell maturation antigen (BCMA) is a cell membrane bound tumor necrosis factor receptor family member that is expressed exclusively on late stage normal and malignant B-cells and plasma cells. Addition of two of its ligands, B-cell activating factor and a proliferation inducting ligand, to normal B-cells cause B-cell proliferation and antibody production. Serum BCMA is elevated among patients with multiple myeloma (MM) and chronic lymphocytic leukemia (CLL), and is a prognostic and monitoring tool for these patients. The first anti-BCMA antibody ( Ab ) was developed in 2007. Recently, biotech and pharmaceutical companies have created various forms of BCMA-directed Abs (naked Abs, Ab drug conjugates, and bispecific Abs) and cellular therapies (chimeric antigen receptor T-cells) with promising clinical results. Areas covered : This BCMA review encompasses full-text publications of original research articles and abstracts presented at hematology/oncology meetings. Expert commentary : The limited preclinical and ongoing clinical studies published to date evaluating BCMA-directed therapies have shown great promise. It has also been demonstrated that BCMA is solubilized and elevated in the blood of MM, Waldenstrom's macroglobulinemia and CLL patients, and is also responsible for the immune deficiency in MM. Reducing circulating levels may improve the efficacy of these treatments.